A comparison of video and accelerometer based approaches applied to performance monitoring in swimming - Callaway, A. J.; Cobb, J. E.; Jones, I. (International Journal of Sports Science and Coaching, 2009)
The aim of this paper is to present a comparison of video- and sensor-based studies of swimming performance. The video-based approach is reviewed and contrasted to the newer sensor-based technology, specifically accelerometers based upon Micro-Electro-Mechanical Systems (MEMS) technology. Results from previously published swim performance studies using both the video and sensor technologies are summarised and evaluated against the conventional theory that upper arm movements are of primary interest when quantifying free-style technique. The authors conclude that multiple sensor-based measurements of swimmers' acceleration profiles have the potential to offer significant advances in coaching technique over the traditional video based approach.